Method for lineage typing of epidemic Renibacterium salmoninarum in Chilean salmon farms. Issue 5 (25th January 2023) - Mora‐Salas, Patricia; Zapararte, Sebastián; Villouta, Pamela; Araya‐León, Henry; Avendaño‐Herrera, Ruben; Melo, Francisco; Mardones, Fernando O.
Abstract: Renibacterium salmoninarum ( Rs ) is the etiological agent of bacterial kidney disease (BKD), which significantly affects farmed and wild salmonids worldwide. Although the whole genome of Rs ( 3.1 million nucleotides) is highly conserved, genomic epidemiology analyses have identified four sub‐lineages from Chilean isolates. A total of 94 Rs genomes from the BIGSdb aquaculture database were aligned and compared using bioinformatics tools, identifying 2199 independent single‐nucleotide polymorphisms (SNPs) spread along the genome. A detailed analysis of the distribution of the SNPs showed five local zones of a length in the range of 10–15 kbp that should be used to unambiguously identify a specific sub‐lineage. Based on the Rs type strain DSM 20767 T, we designed multiplex PCR primers that produce specific amplification products which were further sequenced by the Sanger method to obtain the genotype of the sub‐lineage. For the genetic typing, we evaluated 27 Rs isolates recovered from BKD outbreaks from different fish species and regions of Chile. Based on the findings reported here, we propose the PCR approach as a valuable tool for the rapid and reliable studying of the relationships between Rs isolates and the different sub‐lineages without requiring the sequencing of the entire genome.